2010
DOI: 10.1007/s11596-010-0204-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electric stimulations applied during absolute refractory period on cardiac function of rabbits with heart failure

Abstract: The effects of electric currents applied during absolute refractory period (ARP) on the cardiac function of rabbits with heart failure due to myocardial infarction (MI), and the safety of this method were investigated. Thirty rabbits were randomly assigned equally to 3 groups: sham-operated group, LV-anterior wall cardiac contractility modulation (LV-CCM) group, and septum-CCM (S-CCM) group. A thoracotomy was performed on all the rabbits. Electric pulses were delivered during the ARP on the anterior wall of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, the effects of NES on global contractility, as measured by LV dP/dt max, were positive during NES (23.3 ± 12%, 26.0 ± 9.3%, and 31.3 ± 12.5% for anterior, posterior, and both respectively). Acute improvements in global functional measures have also been demonstrated in dogs with LV dysfunction (through serial coronary micro-embolizations) using the biphasic waveform after 10 min to 6 h of stimulation [24, 25] and more recently in rabbits with heart failure due to myocardial infarction [26]. …”
Section: Electrical Stimulation On the Heartmentioning
confidence: 99%
“…However, the effects of NES on global contractility, as measured by LV dP/dt max, were positive during NES (23.3 ± 12%, 26.0 ± 9.3%, and 31.3 ± 12.5% for anterior, posterior, and both respectively). Acute improvements in global functional measures have also been demonstrated in dogs with LV dysfunction (through serial coronary micro-embolizations) using the biphasic waveform after 10 min to 6 h of stimulation [24, 25] and more recently in rabbits with heart failure due to myocardial infarction [26]. …”
Section: Electrical Stimulation On the Heartmentioning
confidence: 99%
“…These new technologies are developed as a treatment for refractory systolic heart failure of, through electrical stimulation of small, undetectable or sub-threshold electrical impulses to increase and/or synchronize myocardial contractility. Numerous studies have demonstrated the usefulness of CCM to evoke cardiac inotropic effect [24,25,26]. The ability of CCM to improve cardiac function is believed mainly due to enhanced local contraction force and electrical stimulation in different parts of the myocardium may have different efficacies on cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of CCM to improve cardiac function is believed mainly due to enhanced local contraction force and electrical stimulation in different parts of the myocardium may have different efficacies on cardiac function. It is not yet clear and is even still confusing as to what parts of the myocardium stimuli should be applied to achieve the best effects [25,26]. In this study, we compared left ventricle anterior wall stimulation (LVP-CCM) as a mono-ventricular CCM with bi-ventricular CCM.…”
Section: Discussionmentioning
confidence: 99%